Academic Resilience of Students: What Is Its Relationship with Learning Motivation of Islamic Education Students? - Ramadhan, Ahmad Faisal; Baharudin; Azizah, Nurul; Hijriyah, Umi; Susanti, Agus (Universitas Muhammadiyah Sidoarjo, 2025)
You said: Academic background: Student success in higher education is strongly influenced by internal factors such as motivation and psychological resilience. Specific background: In the context of Islamic Education (PAI), students are expected to manage not only academic responsibilities but also spiritual and social demands. Knowledge gap: While prior studies have addressed the relationship between resilience and motivation, few have focused specifically on PAI students. Aim: This study investigates the relationship between academic resilience and learning motivation among PAI students at UIN Raden Intan Lampung. Results: Using a quantitative correlational approach with 81 students, findings show that academic resilience significantly predicts learning motivation (R² = 0.096, p < 0.05), although its effect is modest. Novelty: The research highlights the unique role of spirituality as a resilience component that strengthens intrinsic motivation, especially in religious education contexts. Implications: These results suggest the need to integrate resilience-building programs into PAI curricula and underscore the importance of structured academic and psychological support to enhance student engagement and persistence.Highlight : Academic resilience significantly correlates with learning motivation among Islamic Education students. The strongest motivational factors include spirituality, personal competence, and emotional regulation. Institutions are urged to develop resilience-building programs to sustain student performance. Keywords : Academic Resilience, Learning Motivation, Islamic Education, Student Psychology, Educational